SPATIAL DISORIENTATION TRAINING TO SUPPORT FLYING SAFETY IN INDONESIAN AIR FORCE - Sovian Aritonang; Hendro Yulieanto; Deni Dadang Ahmad Rajab (The Republic of Indonesia Defense University, 2020)
The magnitude of aircraft accidents due to the spatial disorientation (SD) experienced by the aircrew has encouraged efforts to provide optimum training to prevent and minimize those unexpected accidents. In their publication, USAF has stated that SD had caused 15-69% of their aircraft fatal accidents. This study aims to determine the extent of which the SD training program in Aerophysiological Indoctrination and exercise (ILA) of the Indonesian Air Force has been carried out effectively, making it useful for the crew to prevent accidents. The main focus of the study is to analyze the willingness of aircraft crew; leadership support policy, simulator tool condition, and qualification of instructors. This research designed to use a qualitative descriptive approach. Data collections obtained through depth interviews involving Indonesian Air Force aircrews, aviation health experts, instructors officer of Health Service of Indonesian Air Force, and also through the search of publication and related documents. The results show that there are still many aspects required more attention from the Indonesian Air Force authorities; insufficient simulator facilities that are too old and out of Job, inadequate software as the basis of the implementation of the training program, the limited .qualifications of training instructors, and lack of support from higher commands.